Comparison of photocell and Optojump measurements of maximal running velocity - Dolenec, A.; Coh, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Due to additional data on the stride length, the contact and flight times, a combination of photocells and optojump (OJ) measurements are lately being used to measure running velocity. As both systems are used to measure velocity, this research focused to ascertain whether velocity measurement results obtained by either photocells or by OJ are the equivalent. The research involved 17 sprinters (11 male and 6 female). Their average best score in a 100 m run was 11.24 s (+-0.56), the age 19.9 years (+-3.4), height 1.74 m (+- 7.4), weight 65.6 kg (+-7.57). Each of them performed two sprints of 20 meters, flying start. For further analysis, the fastest sprint measured with the photocells was used. The velocity was simultaneously measured by the photocells (Brower timing, USA) and OJ (Microgate, Italy). The photocells were installed at four consecutive, 5 meters long sections. Photocells were installed at a 1.14 meter height. The OJ was installed from the first to the last pair of photocells. In measurements with OJ, foot contact closest to the photocells was used to determine the beginning and the end of an individual section. A t-test for related samples was used to compare the variables measured by photocells and by OJ. The ANOVA test was used to test the differences among the variables that were measured with the same method. In measurements with photocells, the running velocity on the 10- to 15-meter section was 10% higher than the running velocity on 0- to 5-meter section. On the 0- to 5-meter section, the measured velocity was statistically significantly lower than the velocities measured on other sections. In OJ measurements, there were no statistically significant oscillations in velocities as per individual sections. Velocities measured with photocells and OJ statistically significant differed on two sections. The velocity measured with photocells on the 0- to 5-metre section was statistically significantly lower than the velocity measured with OJ. While on the 10- to 15-meter sections, the situation was just the opposite. Regardless of the section length (5, 10, 15, or 20 m), the average speed measured with the photocells was always statistically significantly lower than the average velocity measured with OJ. The results of maximal velocity measurements with single beam photocells installed 1.14 meters high cannot be compared to results of maximal velocity measurement done by OJ in cases when the measurement sections are 5 to 20 meters long. Further researches should be carried out in order to ascertain which of the timing system gives the results that would be closer to the actual centre of mass velocity.